Personalising the student first year experience – an evaluation of a Staff Student Buddy System - Fewster-Young, Nick; Corcoran, Paul (Journal of University Teaching and Learning Practice, 2023)
A student’s transition into higher education or a new learning environment can set the foundation for the remainder of their study, both in perception and academic ability. Mentoring is a transition intervention strategy and most types of these interventions are student peer to peer. However, there is a growing interest in academic involvement in mentoring and consequently this paper is an investigation into the effective implementation of assigning students with an academic staff buddy or mentor in the transition period of their first year of higher education i.e. the Staff Student Buddy System (SSBS). The analysis focusses on using two measures to inform the results by qualitatively analysing the feedback from the students, and quantitatively measuring the difference in academic performance of both student participants and non-participants. The sample of the students come from the University of South Australia, and the qualitative analysis indicated that students enjoyed SSBS, particularly with the ability to ask questions to those that would be teaching them. The quantitative statistical evidence indicated that SSBS could be a positive factor on a student’s Grade Point Average. Overall, the conclusion was that that the combination of the SSBS and these students produced improved academic performance while providing a positive student experience.